2015
DOI: 10.1039/c5cp05582b
|View full text |Cite
|
Sign up to set email alerts
|

High rectification in organic diodes based on liquid crystalline phthalocyanines

Abstract: The optical and electrical properties of mesogenic metal-free and metalated phthalocyanines (PCs) with a moderately sized and regioregular alkyl periphery were investigated. In solution, the individualized molecules show fluorescence lifetimes of 4-6 ns in THF. When deposited as solid thin films the materials exhibit significantly shorter fluorescence lifetimes with bi-exponential decay (1.4-1.8 ns; 0.2-0.4 ns) that testify to the formation of aggregates viaπ-π intermolecular interactions. In diode structures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In solution, = the emission peak is at 451 nm while in solid state a much broader two-peaked emission spectra are observed , with peak positions at 479 and 544 nm in the spin-coated film, and 475 and 550 nm in the nematic glass). The absorption and emission broadening in film and nematic glass compared to the low concentration solution, together with the red shift of the emission spectra, testifies the stronger intermolecular interactions in solid state [12]. The pronounced dominance of the longer-wavelength peak in the nematic glass contrasts with a slight prevalence of the shorter-wavelength peak in the film.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In solution, = the emission peak is at 451 nm while in solid state a much broader two-peaked emission spectra are observed , with peak positions at 479 and 544 nm in the spin-coated film, and 475 and 550 nm in the nematic glass). The absorption and emission broadening in film and nematic glass compared to the low concentration solution, together with the red shift of the emission spectra, testifies the stronger intermolecular interactions in solid state [12]. The pronounced dominance of the longer-wavelength peak in the nematic glass contrasts with a slight prevalence of the shorter-wavelength peak in the film.…”
Section: Resultsmentioning
confidence: 83%
“…We have now found that the [12]phenacene derivative 4 surprisingly shows a monotropic nematic phase when, after melting at 247°C [6], the isotropic liquid is cooled to 241°C. No nematic behavior could be observed with the shorter and longer homologues 2, 3 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the similarity to the lifetime in solution, the 6.90 ns lifetime in the film is attributed to monomeric emission. The shortest lifetime of 0.90 ns can be related to the emission of aggregated species driven by π-π interactions [36], contributing to almost 20% of the total emission of 1. The longer lifetime of 2 in film (3.84 ns) can be attributed to the monomeric emission as it is similar to the value observed in solution, while the shortest lifetime (1.58 ns) of aggregated π-π species dominates with 75.38% of the total emission.…”
Section: Resultsmentioning
confidence: 99%
“…10) Among the liquid crystals, smectic liquid crystals are the most promising, because the charge carrier transport in both liquid-crystalline and crystalline thin films is two-dimensional, 11) which is better than that in discotic liquid crystals with one-dimensional π-stacks for the transport channel in the resulting films. [12][13][14] In fact, polycrystalline thin films fabricated with smectic liquid crystals afford highly excellent FET performance. 15,16) The planar-orientation crystalline thin films have been achieved in liquid-crystal cells, although the films always have a covered surface with thick and rigid glass substrates, 5) which limit their availability for device applications.…”
mentioning
confidence: 99%